Upaya Penanganan Tingkat Perdagangan Satwa Liar oleh Pemeritah Indonesia Pada Tahun 2013-2016 - Ani Khoirunnisa; Pricille Pricille (GLOBAL INSIGHT JOURNAL, 2019)
ABSTRACTWildlife trade is a wild trade in protected animals without regard to the existing rules. Some people are still buying and selling animals protected illegally, both buying and selling transactions that are alive to be maintained , or in the form of animals that have been preseerved. In fact, the trade in these animals has caused considerable losses for Indonesia. This wildlife trade cae is not carried out only by individuals but there is an organized as consumers of every product from wild animals. Therefore one of the efforts made by Indonesia is to conduct various international collaborations, because in responding to the case of wildlife trade, it is not enough only from law enforcement, and involving more than one country, international coopeeration is needed.The research method that writer used is a qualitative method with a descriptive type of research approach that is by describing phenomenas that occur to find out the efforts of the Indonesia government in handling the level of wildlife trade in the period 2013-2016.With the cooperation efforts carried out by the Indonesia government to help cover the shortcomings and constraints faced by the Indonesian government regarding the lack of human resources and also substantial financial resources to overcome the practice of wildlife trade. Keywords: Wildlife Trade, Green Politics, International Cooperation, International Organizations